Nikolai Leskov in the aspect of translation: language game and phraseology - Seliverstova, Elena (Bohemistyka, 2019)
The continuing interest in the artistic word reveals all the new aspects of the study of the writers’ language, the methods of usage of the linguistic units in their works. This article brings together in one focus several problems: the study of the language creativity of N.S. Leskov, manifested in the creation of unforgettable speech portraits of characters, who, in search of expressiveness, realize their creative abilities, using already known words and expressions or creating the new ones. Occasional expressions, used to achieve maximum expressiveness and intensity of the transmitted value, can be read in the same text in different ways. The multiple transformation of stable expressions is especially typical for the writer, therefore it is difficult not only to interpret the author’s phraseology in Leskov’s works, but also to translate. The Czech translators using the principle of functional similarity try to keep ways of usage of the units created by the author and to inform the reader of expressivity, emotional sounding and esthetic functions of the original.